2003
DOI: 10.1017/s1431927603030289
|View full text |Cite
|
Sign up to set email alerts
|

Angioarchitecture of Tumors Induced by Two Different Cloned Cell Lines Established from a Transplantable Rat Malignant Fibrous Histiocytoma

Abstract: Angiogenesis, a biologic process whereby endothelial cells divide and migrate to form new blood vessels, is a key step in tumor growth, invasion, and metastasis. In the present study, we investigated the differences in angioarchitecture between two different tumors induced by cloned cell lines (MT-8 and MT-9), derived from a transplantable rat malignant fibrous histiocytoma, by scanning electron microscopy of vascular corrosion casts. During a 3-week observation period after implantation, the growth of MT-8 tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2005
2005
2007
2007

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…On the other hand, our study could just as well have shown that the 3D power Doppler method was too crude to detect the differences. Earlier studies found a wide heterogeneity of vessel distribution in different parts of tumors38, 39 and in different types of tumor37, 40, 41. Such heterogeneity may explain some of the false‐positive and false‐negative diagnoses using our technique.…”
Section: Discussionmentioning
confidence: 64%
“…On the other hand, our study could just as well have shown that the 3D power Doppler method was too crude to detect the differences. Earlier studies found a wide heterogeneity of vessel distribution in different parts of tumors38, 39 and in different types of tumor37, 40, 41. Such heterogeneity may explain some of the false‐positive and false‐negative diagnoses using our technique.…”
Section: Discussionmentioning
confidence: 64%
“…It plays a critical role in normal and pathological processes, including the growth and the invasion and the metastasis of tumors [23,34]. Tumor vessels present both functional and structural anomalies, which can explain many pathological features observed in tumors such as edema [24,35].…”
mentioning
confidence: 99%